Impacts of natural disasters on supply chain performance - Burkhardt, Mariana (Produktion und Energie, 2021)
Considering the increasing importance of natural disaster events it is inevitable to also focus on their impacts on supply chains as well as their performance impacts on them. The developed approach SCperformND (Supply Chain performance impact assessment of Natural Disasters) demonstrates a methodology to assess those impacts and gives implications for supply chain designs and procurement decisions.